Evaluation Levels of Interleukin-6 in Sera of Iraqi Pregnant and Non-Pregnant Diabetic Women with Dental Caries - Saeed , Husam Mohammed; Nawaf, Raghad Noori; Hussain, Suzan Saadi; Tektook, Nihad Khalawe; Mohammed, Shaymaa Saadi (Journal of Neonatal Surgery, 2025)
Background: The relationship between diabetes mellitus and oral health, particularly the prevalence of dental caries, has garnered increasing attention.Interleukin-6 (IL-6) is a pro-inflammatory cytokine that may play a pivotal role in this association. This study aimed to estimate the serum levels of IL-6 in sera of Iraqi Pregnant and Non-Pregnant Diabetic Women with Dental Caries and compare these levels to those in healthy control. Methods: A total of 50 Iraqi Pregnant Diabetic Women with Dental Caries and compare these levels in healthy control, diabetic patients aged 18-40 years with diagnosed dental caries (with bacteria Streptococcus mutans and Streptococcus sobrinus , Actinomycess spp and lactobacillus spp ) were recruited from outpatient clinic of Al-Yarmouk Teaching Hospital between ( February to October) 2024. A control group of 50 healthy individuals matched for age was also included. Serum samples were collected and analyzed for IL-6 levels using an enzyme-linked immunosorbent assay (ELISA). Results: in current study showed the Body Mass Index (BMI) Results :Results in current study showed body Mass Index (BMI) (28.4 ± 3.6) Compare to healthy control (24.9 ± 2.9), so elevated IL-6 levels in pregnant diabetic women with dental caries (18.60±5.3) compare to non-pregnant diabetic group with dental caries (13.11±3.9), p-value (< 0.001).As well as IL-6 levels between Pregnant diabetic women (17.5 ± 5.2) and healthy (15.8 ± 4.8) also levels of IL-6 non- Pregnant diabetic women(15.8 ± 4.8) and healthy (5.5 ± 1.5) , the differences in the inflammation related to diabetes with dental caries. A p-value of (< 0.01) significant difference in IL-6 levels between diabetic patients and healthy controls,also a strong positive correlation between trimester and IL-6 levels in diabetic patients with dental caries compare to healthy controls. the IL-6 levels tend to increase with age, especially in the Pregnant diabetic group with dental caries have elevated (18.7 ± 5.5) in age group( ≤40years). Conclusion: Elevated serum IL-6 levels in diabetic patients with dental caries suggest a potential link between systemic inflammation and oral health complications.